Test of lepton universality with Λ0b→pK−ℓ+ℓ−Λb0→pK−ℓ+ℓ− decays; Journal of High Energy Physics; Vol. 2020, iss. 5 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich (2020, 2020)
Title screen